DOES CONCENTRATED OWNERSHIP, CASH HOLDING, SHARE PRICE AND LIQUIDITY AFFECT COMPANY PERFORMANCE? - Aryanti Putri; Maharani Aulia Akam; Farah Margaretha Leon (Jurnal Bisnis dan Akuntansi, 2024)
The purpose of this study is to obtain empirical evidence regarding the effect of independent variables which are concentrated ownership, stock price volatility, cash holdings and liquidity on company performance. This study used manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020-2022. The number of research samples is 36 companies with a total of 108 data that match the criteria using a purposive sampling method. The research results obtained are that concentrated ownership and liquidity positively affect the company's performance. The variables of stock price volatility and cash holdings have no effect on company performance. The implication of this research that has been done is to provide direction for financial managers in terms of using debt to achieve company goals. For investors, it is better to choose a company that has high liquidity.